Chemical composition of leaf essential oil of Lantana camara L. from Bangladesh - Chowdhury, Jasim Uddin; Nandi, Nemai Chandra; Bhuiyan, Md Nazrul Islam (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Essential oil of fresh matured leaves of Lantana camara L. growing in Bangladesh were analyzed by GC-MS technique. Sixty two compounds were identified in the oil. The major constituents identified include caryophyllene (13.57%), α-caryophyllene (11.76%), germacrene D (10.88%), isocaryo-phyllene (9.59%), Î³- muurolene (6.85%) and Î³-elemene (5.65%). Â Key words: Lantana camara, Essential oil, Caryophyllene DOI = 10.3329/bjb.v36i2.1513 Bangladesh J. Bot. 36(2): 193-194, 2007 (December)